Pengaruh Kecerdasan Emosional, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Badan Perencanaan Pembangunan Daerah - Adnan Rajak; Nurlaila Nurlaila; Chintia Mumulati (Jurnal Manajemen Sinergi, 2019)
The Problem in this study are : (1) Does Emotional Intelligence affect the performance of employees at the Regional Development Planning Board of North Maluku Province ?, (2)Does compensation affect the performance of employees at the Regional Development Planning Board of North Maluku Province ?, (3) Does the work discipline affect the performance of employees in the Regional Development Planning Board of North Maluku Province ?, (4) Does Emotional Intelligence, Compensation and Work Discipline have a simultaneous effect on employee performance at the Regional Development Planning Board of North Maluku Province?The purpose of this study was to determine the effect of Emotional Intelligence, Compensation, and Work Discipline both partially and simultaneously on Employee Performance at the Regional Development Planning Agency of North Maluku Province. The analysis model used to test the hypothesis is multiple linear regression analysis and the research method used is explanatory research with a quantative approach and a population of 82 respondents. With data processing techniques using SPSS 16 for windows.The results of the study prove that: (1) Emotional Intelligence has a positive and significant influence on Employee Performance, which means that the application of good emotional intelligence, the higher the level of employee performance. (2) Compensation has a positive and significant effect on Employee Performance, which means that the better compensation is given, the higher the level of employee performance. (3) Work Discipline has a positive and significant effect on Employee Performance, which means that the better the work discipline given, the higher the level of employee performance. With simultaneous results, the three variables have a positive and significant effect on Employee Performance with corrected R2 (R Square) value of 0.403 or 40.3%.